Studies on Molar Volume of Alkali Metal Complexes in Non-Aqueous Solvents - Singh, T.K.; Kumar, Binod; Singh, Punam (Asian Journal of Chemistry, 2010)
The apparent molar volume ( Φv) of M-BAN-Ox for variousconcentrations of salt M-BAN have been determined in methanoland 95% ethanol at 300 K, where M-BAN = Na and K salt of1-benzene-azo-2-naphthol and Ox = oxalate ion. We have observedthat in methanol as concentraton of salt increases (5 to 15%) theΦv decreases; after that no change in Φv takes place when weincrease the concentration of salt in the solution of oxalate ion. Inethanolic medium, Φv shows decreasing trend as concentration ofsalts increases from 5 to 25%. It shows that in methanol the complexforming tendency terminates at 15% and above concentrations whilein ethanolic medium the soluble complex formation tendency isretained even upto 25% concentration. This change of Φv is muchmore pronounced in the case of corresponding potassium complexesthrowing light on the fact that potassium complexes are more stablecompared to their corresponding sodium complexes.